2018
DOI: 10.3390/su10072464
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Energy Taxes and the Validity of the Residential Electricity Environmental Kuznets Curve in the European Union

Abstract: To achieve the energy targets, energy policy of the European Union (EU) is trying to discourage residential electricity consumption employing different measures but without worsening the quality of life and jeopardizing its economic growth and development at the same time. This paper aims to directly and indirectly explore the effects of energy taxes on household electricity consumption and test the validity of the household electricity environmental Kuznets curve (EEKC) in a multivariate setting and a system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 46 publications
(70 reference statements)
4
11
0
Order By: Relevance
“…The empirical results claimed that imposed carbon-tax might reduce the emissions level by 1% with respect to the forcasted period 2014 to 2024. For the case of European countries, Borozan [25] claimed that the energy related taxes signficantly affect the electricty use more efficiently by affecting the energy prices directly and indirectly.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The empirical results claimed that imposed carbon-tax might reduce the emissions level by 1% with respect to the forcasted period 2014 to 2024. For the case of European countries, Borozan [25] claimed that the energy related taxes signficantly affect the electricty use more efficiently by affecting the energy prices directly and indirectly.…”
Section: Literature Reviewmentioning
confidence: 99%
“…AT, BE, BG, HR, CZ (2) , DE, EE, FI, FR, DE, EL, HU, IE, LV, LU, MT, NL, PL, PT, RO, SK, SI, ES, SE, UK CY (4) , IT (3) LT (1)(3) AT, BE, BG, HR, CZ, DE, EE, FI, FR (2) , DE, EL, HU, IE, LV, LT, LU, MT, NL, PL, PT, RO, SK, SI, SE, UK CY (4) , IT AT, BE, BG, HR, CY, CZ, DE, EE, FI, DE, EL, IE, IT, LV, LU, MT, NL, PL, PT, RO (2) , SK, SI, SE, UK HU (1)(4) , LT (4) , FR MT (4) , SE (1) 3IT (1)(4) AT, BE, BG, HR, CY, CZ, DE, EE, FI, FR, DE, EL, HU, IE (2) , LV, LU, NL, PL, PT, RO, SK, SI, SE, UK LT (4) , MT (1) 4IT 1 In the case of Granger causality between energy taxes and renewable energy consumption, we found weak statistical evidence of a negative correlation between taxes and renewable energy in Hungary (with both types of models used for estimation). Meanwhile, in Lithuania, we found strong and in France weak and positive evidence (just with the log-log type of the model) that showed that in these countries, an increase in energy taxes Granger-caused an increase in renewable energy consumption.…”
Section: Time Series Data Analysismentioning
confidence: 99%
“…Environmental taxes are taxes imposed due to environmental reasons, and they provide an incentive to reduce certain environmental impacts. Environmental taxes affect resource consumption or emissions quantities by increasing the price of chargeable products [1][2][3] and are the tools most used in environmental policy. The main aim of these taxes is to change market prices to internalize environmental harms [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, implementing specific government programs will decrease it. For example, the share of energy tax revenues in GDP turns out to be negative and significant in the BMA settings, meaning that an energy tax is an effective policy tool for influencing industrial energy consumption directly in contrast to the residential sector [44]. Evidently, since an energy tax increases business costs, it motivates them to reduce energy consumption, improve energy efficiency, and use more cleaner and greener energy and sustainable practices.…”
Section: Determinants Of Industrial Energy Usementioning
confidence: 99%